Pengembangan Multimedia Pembelajaran Interaktif berbasis Scratch pada Materi Membandingkan Nilai Pecahan - Fatimatuz Zahro Octavia; Kartika Yulianti (Universitas PGRI Adi Buana Surabaya, 2022)
Mathematics is an abstract science, so we need media that can bridge things from contextual to abstract. The use of interactive learning multimedia that provides visualization and interactions in it can help students understand mathematics learning better. The purpose of this research is to produce an interactive Scratch-based interactive mathematics learning multimedia that meets the valid and practical requirements to facilitate the learning of VII graders of SMP/MTs in the matter of comparing fractions. The method used is Research and Development. Collecting data using interviews, observations, literature studies, and validation questionnaires. Based on the results of the validation questionnaire, it was concluded that the learning media was feasible to use and the learning media were considered to be able to facilitate the learning of mathematics in the matter of comparing fractions.